Energy Management of an Autonomous Photovoltaic System under Climatic Variations - Njeh, Khouloud; Zdiri, Mohamed Ali; Ben Ammar, Mohsen; Rabhi, Abdelhamid; Ben Salem, Fatma (Engineering, Technology & Applied Science Research, 2023)
Predictable and unpredictable variations are two major causes of renewable energy-related intermittency. Such a drawback could be overcome by applying new energy management strategies, particularly storage systems. This paper investigates the feasibility of introducing a photovoltaic management string, enabling the maintenance of continuous energy supply storage capacity. Accordingly, the PV system is liable to perform at maximum efficiency following the implementation of an MPPT-controlled DC/DC boost converter of the Perturb and Observe (P&O) type. Most of the energy-management approaches target goals lie mainly in optimizing the energy resources’ operational and storage capacities. The current MATLAB/Simulink-based simulation study achieved results that turned out to testify well to the advanced design’s high performance and efficiency in maintaining the load’s energy autonomy while increasing the battery’s life span.